2019
DOI: 10.1200/jco.2019.37.15_suppl.9021
|View full text |Cite
|
Sign up to set email alerts
|

S1507: Phase II study of docetaxel and trametinib in patients with G12C or non-G12C KRAS mutation positive (+) recurrent non-small cell lung cancer (NSCLC).

Abstract: 9021 Background: KRAS+ NSCLC remains the most common genetically defined subset of NSCLC. Despite promising pre-clinical data, MEK inhibitors have failed to provide meaningful clinical benefit both as single agents and in combination with chemotherapy in KRAS+ NSCLC patients. Pre-clinical data suggest that efficacy of MEK inhibitors in KRAS+ NSCLC differs based on specific KRAS mutations such as G12C and by status of p53 or LKB1 mutations. We conducted a phase II study to assess the efficacy of docetaxel plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This is consistent with the findings in a previous study [39]. In addition, there have been a number of clinical trials involving trametinib alone [45] or in combination with other drugs [46] for non-small cell lung cancer. Another drug, gefitinib, targets the epidermal growth factor receptor (EGFR) by inhibiting the tyrosine kinases associated with EGFR [47].…”
Section: Use Case-nodetic Examplesupporting
confidence: 92%
“…This is consistent with the findings in a previous study [39]. In addition, there have been a number of clinical trials involving trametinib alone [45] or in combination with other drugs [46] for non-small cell lung cancer. Another drug, gefitinib, targets the epidermal growth factor receptor (EGFR) by inhibiting the tyrosine kinases associated with EGFR [47].…”
Section: Use Case-nodetic Examplesupporting
confidence: 92%
“…The ASCO systematic review found two studies, one published RCT and the second, a single-arm study, including those with KRAS mutations (the study by Carter et al also included patients with KRAS wild type) and previous treatment. 65,66 The study by Carter et al investigated erlotinib versus selumetinib plus erlotinib versus selumetinib. The primary outcome was RR, and the results were minimal.…”
Section: Krasmentioning
confidence: 99%
“…In a phase II trial, trametinib as a monotherapy showed RR and PFS similar to docetaxel in previously treated KRAS -mutant NSCLC (49). Another phase II study with KRAS -mutant NSCLC (n = 54, including 19 with G12C, 9 with G12D, 9 with G12A) documented a trend toward worse PFS (HR = 1.86, p = 0.06) and survival (HR = 1.80, p = 0.14) in G12C patients compared to non-G12C patients (50). Trametinib plus docetaxel had a RR of 33% and median survival of 11.1 months in patients with recurrent KRAS -mutant NSCLC.…”
Section: New Horizons For Treating Kras-mutant Lung Cancermentioning
confidence: 99%